A Custom-Fabricated Device for Chairside Organization of Multiple Implant Components - Randy Toothaker, DDS,1 Deborah Ashcraft, DMD,2 Ioannis Soultanis, DDS,3 and (Journal of Prosthodontics, 2003)
Organizing multiple and varied implant components in preparation for providing treatment for a patient with a complex implant prosthesis can be a challenge to even the most experienced practitioner